Does ICT Adoption Influence Public Service Motivation? The Moderating Roles of Leadership Support and Digital Literacy - Bello, Muhammed Lawan; Adejumo, Abdulhakeem; Akintola, Muslim Akinbola; Ameen, Abdullateef; Amosa, Jimoh Rafiu; Suleiman, Ahmed Aremu; Isiaka, Sulu Babaita; Abdulkareem, Zulfah Jumoke; AbdulKareem, Abdulrazaq Kayode (Advances in Humanities and Contemporary Studies, 2025)
This study explores the factors influencing the adoption of new technologies in public service organizations, focusing on the role of individual perceptions and organizational support. Using a survey-based approach, the research examines the relationships between Perceived Usefulness, Perceived Ease of Use, Behavioural Intention to Use, Public Service Motivation, Leadership Support, and Digital Literacy. The data was collected from employees of selected Ministries in Kwara State, Nigeria and analysed using PLS-SEM. The findings highlight the significant impact of PU and PEOU on BIU, with both perceived usefulness and ease of use being crucial in shaping employees’ intention to adopt new systems. Additionally, leadership support plays a critical role in fostering a positive attitude toward technology adoption, especially when public service motivation is a driving factor. The study also emphasizes the importance of digital literacy in ensuring that employees possess the necessary skills to effectively use new technologies. These results suggest that public service organizations should adopt a holistic approach to technology implementation, focusing on designing user-friendly systems, providing leadership support, and investing in digital literacy programs. By addressing these factors, organizations can enhance technology adoption, improve employee engagement, and ultimately increase the efficiency and quality of public service delivery. The study offers practical implications for organizations seeking to successfully implement digital systems and drive organizational change.